Mathematical Modeling of Solar Air Heater with Different Geometries - Kumar, Ashish (My University, 2009)
The intent of the present study is to study the behaviour of counter flow solar air heaters and to compare their performance with the conventional air heaters under different conditions, obtained by changing the various governing parameters like air mass flow rate, inlet air temperature, spaciong between top cover and absorber plate and intensity of solar radiation.
Keywords: counter flow; SOLAR AIR HEATER; FINITE ELEMENT ANALYSIS